2013
DOI: 10.1186/1129-2377-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of cluster headaches in China – a clinic-based study

Abstract: BackgroundThe clinical profile of cluster headache in Chinese patients have not been fully studied.MethodsThe classification and clinical features of 120 consecutive patients with cluster headache (105 males, 15 females; mean age, 34.9 ± 10.5 years) visiting at International Headache Center from May 2010 to August 2012 were analyzed.ResultsPatients came from 16 different regions of China. Mean age at onset of cluster headache was 26.7 ± 10.9 years. Only 13 patients (10.8%) had previously been diagnosed with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
93
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(121 citation statements)
references
References 32 publications
24
93
4
Order By: Relevance
“…Typical aura was found in 7.0% of participants, which lies within the range of other studies, in which aura prevalence varied from 0 to 23% 2, 13, 18, 19, 20, 21, 22…”
Section: Discussionsupporting
confidence: 86%
“…Typical aura was found in 7.0% of participants, which lies within the range of other studies, in which aura prevalence varied from 0 to 23% 2, 13, 18, 19, 20, 21, 22…”
Section: Discussionsupporting
confidence: 86%
“…Cluster headache patients also often report that alcohol intake is able to trigger headache and cluster periods . In a Chinese population of cluster patients, about 56% of the patients reported that alcohol was a trigger for their headache . A German study of cluster headache found that 50% of the patients reported that alcohol triggered attacks, and 70% of these patients described that red wine was the triggering alcoholic beverage.…”
Section: Review Of Studies With Discussion Of Important Questions Andmentioning
confidence: 99%
“…11 Despite the decreasing male to female ratio suggested in Western studies, reports in China, Taiwan, Japan, and Korea still indicated high male predominance of CH in Asia. [13][14][15][16] However, studies investigating clinical features of CH in women are scarce in the Asian population. Therefore, the aim of this study was to describe differences in clinical characteristics and demographic features between the sexes using data from the Korean Cluster Headache Registry (KCHR), which prospectively enrolled patients with CH.…”
Section: Introductionmentioning
confidence: 99%